2021
DOI: 10.2147/ndt.s331442
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Affect Patient Attrition in Buprenorphine Treatment for Opioid Use Disorder: A Retrospective Real-World Study Using Electronic Health Records

Abstract: To describe attrition patterns of opioid use disorder (OUD) patients treated with buprenorphine (BUP) and to assess how clinical, sociodemographic, or BUP medication dosing features are associated with attrition. Patients and Methods: Electronic health records of adults (16+ year-olds) with OUD treated with BUP from 23 different substance use or mental health care programs across 11 US states were examined for one year following BUP initiation in inpatient (IP), intensive outpatient (IOP), or outpatient (OP) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…We estimated that individuals treated with buprenorphine would be 4 times less likely than those not receiving buprenorphine to unlink from care. 75 Treatment retention did not differ among the strategies.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…We estimated that individuals treated with buprenorphine would be 4 times less likely than those not receiving buprenorphine to unlink from care. 75 Treatment retention did not differ among the strategies.…”
Section: Methodsmentioning
confidence: 87%
“…For the BUP and BUP plus HR strategies, we assumed 100% of PCPs would offer buprenorphine at their visits, but patients had a 30% probability of accepting it. We estimated that individuals treated with buprenorphine would be 4 times less likely than those not receiving buprenorphine to unlink from care . Treatment retention did not differ among the strategies.…”
Section: Methodsmentioning
confidence: 98%
“…This theory is reinforced by the fact that dissociative NMDA receptor antagonists such as ketamine, PCP and dextromethorphan/ dextrorphan (at large overdoses) induce a psychotic state more rapidly than dopaminergic stimulants, even at recreational doses. [10] TREATMENT: Treatment includes a combination of medication and counselling. Drugs that are effective in reducing the symptoms are Aripiprazole, Asenapine, Brexpiprazole, Clozapine, Iloperidone, Lurasidone, Cariprazine, Olanzapine, Paliperidone and its palmitate, Quetiapine.…”
Section: Neil1mentioning
confidence: 99%
“…Rentsch et al [54] showed that rapid escalation dose trajectories lead to greater risk for OUD compared to those that escalated at lower rates. OUD treatment medications (e.g., buprenorphine) are useful for examining prescription patterns associated with treatment attrition [55]. Other data modalities are readily available for use.…”
Section: Health Systems-based Cohortsmentioning
confidence: 99%